PERAN KEPALA SEKOLAH SEBAGAI ADMINISTRATOR PENDIDIKAN BERBASIS KEARIFAN LOKAL PAPUA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SD TERPENCIL (STUDI DI DISTRIK KAMBRAU, PAPUA BARAT) - Maria Placida Iwitiyu; Sri Handayani; Eva Dianawati Wasliman (STKIP Subang, 2026)
Low student learning motivation in remote elementary schools is often caused by geographical barriers and sociocultural conflicts, as seen in the enrollment decline at SD YPPK Kambrau, Kambrau District, West Papua, from 73 students (2024) to 65 (2025). This study analyzes the role of the school principal as educational administrator in enhancing learning motivation through integration of Papuan local wisdom. Employing a qualitative phenomenological approach and intrinsic case study, data were collected via in-depth interviews, participatory observation, and document analysis involving the principal, two teachers, and parents. Findings reveal four key administrative functions: (1) participatory planning based on motivation analysis, (2) adaptive instruction aligning academic schedules with customary seasons, (3) development-oriented evaluation, and (4) transforming environmental obstacles into contextual learning opportunities. The novelty lies in a contextual transformational leadership model integrating Papuan customs, fulfilling students’ psychological needs according to Self-Determination Theory (autonomy, competence, relatedness). Implications emphasize that educational administration effectiveness in 3T regions depends on managerial flexibility and respect for local wisdom, supporting SDGs Goal 4 and the context-based Merdeka Curriculum.